Paper domes and shelters: Prototypes - Latka, Jerzy F. (A+BE | Architecture and the Built Environment, 2018)
This part of the dissertation is dedicated to the practical approach to cardboard as a building material through prototyping. Taking a practical approach here means conducting research by design and prototyping architectural structures in which paper and its derivatives are used as the main structural material. The theoretical research and knowledge presented in the previous chapters of the dissertation will be now used as input. The research by design and the realised prototypes will guide us to the solution that answers the question to what extent cardboard can be used as a suitable building material for emergency architecture. The research and development of cardboard architecture used as input for this dissertation were derived from research previously conducted at TU Delft’s Faculty of Architecture. The Cardboard in Architecture research group, which was set up in the department of Building Technology in 2003 and ceased to exist in 2008 due to the great fire that destroyed the building of TU Delft’s Faculty of Architecture (13 May 2008), made a great contribution to this research. The fundamental and technical research was included in the previous chapters. The designs and development of products in the form of prototypes of cardboard structures are presented in this chapter.